Ultrasonographic elastography in the evaluation of normal and pathological skin – a review - Ambroziak, Marcin; Pietruski, Piotr; Noszczyk, Bartłomiej; Paluch, Łukasz (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2019)
The aim of this review article is to discuss the role of ultrasonographic elastography, a technique used to quantify tissue stiffness, in the evaluation of normal and pathological skin. A growing body of evidence suggests that elastography may be used for the diagnosis and monitoring of skin pathologies, in particular tumors, and fibrotic and sclerotic processes. Our knowledge about the elastographic parameters of normal skin is sparse, which together with the lack of reference values for cutaneous stiffness constitutes a serious limitation to the use of elastography in some medical disciplines, including aesthetic medicine.